2014
DOI: 10.4049/jimmunol.1303485
|View full text |Cite
|
Sign up to set email alerts
|

Immunophilins Control T Lymphocyte Adhesion and Migration by Regulating CrkII Binding to C3G

Abstract: Crk adaptor proteins are key players in signal transduction from a variety of cell surface receptors. CrkI and CrkII, the two alternative spliced forms of CRK, possess an N-terminal Src homology 2 domain, followed by a Src homology 3 (SH3) domain, whereas CrkII possesses in addition a C-terminal linker region plus a SH3 domain, which operate as regulatory moieties. In this study, we investigated the ability of immunophilins, which function as peptidyl-prolyl isomerases, to regulate Crk proteins in human T lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…On the contrary, inhibitors of immunophilins, such as CsA and FK506, inhibited the association between CrkII and C3G, suppressing T cells to adhere to fibronectin-coated surfaces to migrate toward the stromal cell-derived factor 1␣ chemokine. Our data demonstrate that immunophilins regulate CrkII activity in T cells and suggest that CsA and FK506 inhibit selected effector T cell functions via a CrkII-dependent mechanism [135]. The Itk-CypA and CrkII-CypA regulatory interactions clearly place CypA among the signaling molecules that regulate signaling pathways downstream of activated TCR.…”
Section: T Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, inhibitors of immunophilins, such as CsA and FK506, inhibited the association between CrkII and C3G, suppressing T cells to adhere to fibronectin-coated surfaces to migrate toward the stromal cell-derived factor 1␣ chemokine. Our data demonstrate that immunophilins regulate CrkII activity in T cells and suggest that CsA and FK506 inhibit selected effector T cell functions via a CrkII-dependent mechanism [135]. The Itk-CypA and CrkII-CypA regulatory interactions clearly place CypA among the signaling molecules that regulate signaling pathways downstream of activated TCR.…”
Section: T Cellsmentioning
confidence: 95%
“…In contrast, in the trans conformation CrkII-SH3N domain is in an open, uninhibited conformation. Moreover, we have shown that CrkII interacts with immunophilins CyPA, CyP40 and FKBP12 in human leukemic T cells [135]. In addition, presence of CyPA increased CrkII association with its binding partner C3G, enhancing the adhesion and migration of T cells.…”
Section: T Cellsmentioning
confidence: 97%
“…Teffs were activated for 24 h with anti‐CD3 (clone S4.1 (AKA7D6)) and their adhesion to fibronectin was analyzed according to the technique described previously (Nath et al, ). 2 × 10 5 cells/ml treated with pantethine at 1 mM or not treated (controls) were labeled with CFSE then washed and suspended in RPMI medium without red phenol containing 0.1% BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Crk interaction with the guanine nucleotide-exchange factor (GEF), C3G, imposes the conversion of the small GTPase, RAP1, to an active GTP-bound protein, which in turn leads to activation of the LFA-1 integrin and increases T-cell adhesion. Activation of this “inside-out” signaling pathway, which promotes integrin-mediated T-cell adhesion, is sensitive to a regulation by immunophilins ( 14 ). GEF-mediated activation of Rap1, which is essential for upregulation of the integrin receptors, can also be mediated by a WASP family verprolin-homologous protein-2 (WAVE2)-regulated CrkL-C3G complexes ( 15 ) as well as by other Crk-independent pathways ( 16 ).…”
Section: The Structure and Binding Partners Of Crkmentioning
confidence: 99%
“…More recent studies demonstrated that human T-cell-derived CrkII, but not CrkI, can physically interact with representatives of two families of PPIases, CypA and FK506 binding protein (FKBP), collectively termed immunophilins ( 14 ). In vitro coincubation of CypA with human T-cell-derived CrkII increased CrkII binding to C3G while immunophilin inhibitors [such as cyclosporine A (CsA) and FK506] downregulated CrkII binding to C3G, suggesting that CrkII-C3G interaction may be subjected to a regulation by immunophilins ( 14 ). This assumption was supported by fluorescence resonance energy transfer (FRET) studies of Jurkat T cells transfected with PICCHUx, a chimeric plasmid encoding the human CrkII 1-236 sandwiched between cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP).…”
Section: Conformation Function and Expression Regulation Of Crk Adamentioning
confidence: 99%